Variations in the microbial community of biofilms under different near-wall hydraulic shear stresses in agricultural irrigation systems. Issue 1 (2nd January 2020) - Hou, Peng; Wang, Tianzhi; Zhou, Bo; Song, Peng; Zeng, Wenzhi; Muhammad, Tahir; Li, Yunkai
Abstract: The hydraulic characteristics along agricultural irrigation pipelines directly affect the local near-wall hydraulic shear stress and biofilm accumulation. However, the variations in the microbial community during the process remain unknown. Based on the Couette-Taylor reactor, a device was developed to accurately control the hydraulic shear stress. The results indicated that the near-wall hydraulic shear stresses showed quadratic correlations with microbial contents (represented by phospholipid fatty acids r  > 0.77, p  < 0.05), and the maximum values were obtained under the shear stresses of 0.20-0.35 Pa. For two types of treated wastewater, the mutual operational taxonomic units among different shear stress treatments showed good consistency (>185). Their corresponding response in the microbial community was represented by the quantitative correlations between the near-wall hydraulic shear stresses and the polymorphism indices ( r  > 0.82, p  < 0.05). Among the microorganisms, Firmicutes at the phylum level were significantly affected by the shear stress and significantly influenced the biofilm accumulation process.